2021
DOI: 10.3390/ijms22168827
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Viscous Media Effects on Elementary Steps of Bacterial Bioluminescent Reaction

Abstract: Enzymes activity in a cell is determined by many factors, among which viscosity of the microenvironment plays a significant role. Various cosolvents can imitate intracellular conditions in vitro, allowing to reduce a combination of different regulatory effects. The aim of the study was to analyze the media viscosity effects on the rate constants of the separate stages of the bacterial bioluminescent reaction. Non-steady-state reaction kinetics in glycerol and sucrose solutions was measured by stopped-flow tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…A concentration of 30% was used, which corresponded to 0.99 M of sucrose and gave more than a threefold higher viscosity as compared with the buffer. From the kinetic curves in Figure 1 , one can see that the reaction noticeably slows down in a more viscous medium for both luciferases, which is due to the diffusion control of some reaction steps [ 24 ]. The change of kinetic parameters in sucrose solution over the entire temperature range is shown in Figure 2 and Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A concentration of 30% was used, which corresponded to 0.99 M of sucrose and gave more than a threefold higher viscosity as compared with the buffer. From the kinetic curves in Figure 1 , one can see that the reaction noticeably slows down in a more viscous medium for both luciferases, which is due to the diffusion control of some reaction steps [ 24 ]. The change of kinetic parameters in sucrose solution over the entire temperature range is shown in Figure 2 and Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, distinct temperature dependences of k decay for two luciferases could be caused by two reasons: (i) by a stronger destabilizing effect on peroxyflavin intermediate in V. harveyi reaction and/or (ii) by temperature influence on the others than k dd rate constants which could be more pronounced in the V. harveyi reaction due to their high contribution into k decay . Earlier, we demonstrated that for the reaction of P. leiognathi luciferase in the presence of sucrose the rate of the dark decay of peroxyflavin intermediate becomes lower, while the rate of the formation of an electronically excited intermediate increases as compared with the buffer [ 24 ]. This could underlie the contrasting changes of k decay observed for two luciferases at 40–45 °C in a sucrose solution ( Figure 2 c,d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…catalytic activity. For Photobacterium leiognathi luciferase it was revealed that integral intensity of the reaction changes in the presence of different cosolvents as follows: sucrose > sorbitol > glucose > glycerol > ethylene glycol that correlates with the relation of hydrodynamic radii of the cosolvent molecules: 5.2 > 3.9 > 3.6 > 3.1 > 2.6 (Å) [2]. Moreover, sucrose increases catalytic constant of excited state intermediate formation up to 5-fold unlike other cosolvents.…”
mentioning
confidence: 99%